Faktor-Faktor yang Berhubungan dengan Kejadian Preeklamsia di RSUD Martapura Okut Tahun 2020 - Pegi Malinda Agustina; Diah Sukarni; Rizki Amalia (Universitas Batanghari Jambi, 2022)
Preeclampsia is a disease that is directly caused by pregnancy, the cause of which is still not known with certainty. According to WHO, MMR is still very high, around 810 women die from complications related to pregnancy or childbirth worldwide every day, and about 295,000 women die during and after pregnancy and childbirth. Several risk factors for the incidence of preeclampsia are occupation, maternal age, parity, gestational age, history of hypertension, multiple pregnancy. Mothers who have multiple risk factors and have had preeclampsia before have a 20% risk of developing preeclampsia. The purpose of this study was to determine the relationship between occupation, maternal age and parity with the incidence of pre-eclampsia at the Martapura OKUT Hospital in 2020. The research method used an analytical survey. The population in this study were all pregnant women who had their pregnancy checked at the Martapura OKUT Hospital in January-December 2020, totaling 1,362 people. The sample in this study was some pregnant women who checked their pregnancy at the Martapura OKUT Hospital in 2020, namely 93 respondents who were taken by random sampling. Data analysis using univariate analysis and bivariate analysis using chi square test. The results of the study showed that there was a relationship between work, age and parity with the incidence of pre-eclampsia at the Martapura Hospital OKUT in 2020. The conclusion was that there was a relationship between occupation, age and parity with the incidence of preeclampsia. eclampsia at the Martapura OKUT Hospital in 2020. It is hoped that the results of this study can be an illustration for the hospital to be able to further improve health services, especially dealing with pregnant women with preeclampsia.